Highlighting the Critical Features of Virtual School in Developing Nation - Mohammed Hussein, Raed; Hajem Glood, Salih; Abduladheem Kamil, wisam (International Journal of Engineering and Technology, 2018)
In the recent years, the high quality of communication technologies enhanced the learning manners and support the interactions among educational stakeholders (teacher, student, managements of schools and parents). With these advantages in the current modern technologies, the present electronic school features do not provide all the requirements of students and educational institutions, due to the varying studentsâ€™ needs, goals, backgrounds, knowledge levels, and learning capabilities. Moreover, the previous studies uncover some weaknesses in the existing electronic learning systems, such as lack of interaction among stakeholders and the difficulty of supporting cooperative work. As for features model, there is scarcity in the appropriate properties of the electronic school feature model to develop the virtual learning specifically for the secondary school. Based on these arguments, this study sought to propose features model of electronic school to link stakeholders in the educational process and fill the gap in the previous literature. With regard to data collection, the secondary and primary data were exploited to achieve the aim of this study. The results of this empirical study can be harnessed to design a comprehensive features model of electronic secondary school for particular education institutions and other conflict areas to complement the existing traditional classrooms.Â Â